Anesthesiological acute pain therapy in Germany: telephone-based survey - Lassen, C L; Link, F; Lindenberg, N; Klier, T W; Graf, B M; Maier, C; Wiese, C H R (Der Anaesthesist, 2013)
The last survey of anesthesiological acute pain therapy in Germany was conducted in 1999. Since then new organisational as well as therapeutic aspects have developed. Amongst others the operation and procedures key (OPS) figure 8-919 complex acute pain therapy has been introduced in the German medical billing system, with the restriction that it cannot currently be redeemed. There is an ongoing debate on the role of epidural analgesia in acute pain therapy and new oral medication concepts have been established. Therefore a survey of the present state of acute pain therapy in Germany was conducted. Based on a list of all 1,356 hospitals in Germany a randomized list of 412 hospitals was generated. Out of these 412 hospitals those with anesthesiology departments (378 hospitals) were contacted via telephone and asked to participate in the survey. Out of the 378 hospitals 285 (75.4 %) agreed to take part. The survey consisted of a questionnaire containing closed and open questions regarding organisational and therapeutic aspects of acute pain therapy. The ethics committee of the University of Regensburg rated the survey as not being subject to approval due to the lack of personal patient data. Of the participating hospitals 183 (64.2 %) had an acute pain service (APS) and of these 107 (58.5 %) met the quality criteria of the OPS 8-919. This figure however, was only consistently documented by 40 (37 %) APSs. Epidural analgesia (EA) was offered by 275 (96.5 %) hospitals and patient-controlled intravenous analgesia (PCA) by 255 (89.5 %). Likewise, 255 (89.5 %) hospitals used controlled-released opioids in acute pain therapy. Concerning EA, the medications most used were sufentanil as an opioid and ropivacaine as a local anesthetic in255 (92.7 %) of the hospitals with EA for sufentanil and 253 (92 %] for ropivacaine. An EA was offered on regular wards in 240 (87.3 %) hospitals. Uncertainty existed about concrete limits for coagulation values before removal of an epidural catheter. The opioid most utilized in PCA was piritramide with some hospitals using morphine or oxycodone (92.2 %, 9.4 % and 9.4 %, respectively). Other opioids, such as hydromorphone and tramadol were rarely used and remifentanil was not used at all. Oral medication was widely used with metamizole being the non-opioid analgesic and oxycodone/naloxone the controlled-release opioid being prescribed the most. New antiepileptic drugs, such as gabapentin or pregabalin were rarely employed in acute pain therapy. Since 1999 the number of hospitals that have implemented an APS has risen from 36.1 % to 64.2 %. The lack of consistent documentation of the OPS 8-919 will probably not increase the likelihood that it will become redeemable in the near future. Certain therapy methods, such as EA and PCA were still well established with oral therapy gaining in significance. The uncertainty regarding limits for coagulation values before removal of an epidural catheter could perhaps be reduced by a statement from the German Society of Anesthesia and Intensive Care.